Speaking up, speaking out : lived experiences of non-tenure track faculty in writing studies - Edwards, Jessica, 1984-; McGuire, Meg (Professor); Sanchez, Rachel (Utah State University Press, an imprint of Univeristy Press of Colorado, 2021)
"Addresses the experiences of those in the non-tenure-track faculty (NTTF) trenches through storytelling and reflection. By connecting NTTF voices from various aspects of writing studies, offers fresh perspectives and meaningful contributions, imagining the possibilities for contingent faculty to be valued and honored in educational systems that often do the opposite."--